Bologna : A Sustainable Culture (Volume 8) - Carbonaro, Gianni; Pancotti, Chiara; European Investment Bank; European Investment Bank (European Investment Bank, 2019)
Bologna$1 (Bs unique political and cultural history helped it forge ahead of most Italian cities with strategic investments in services, health care and education. How well does its focus on sustainability in a range of areas set it up for continued success? This essay provides an overview of the development of the Bologna metropolitan region in recent decades, emphasising the role of urban policy and investment within a wider territorial context $1 (BEuropean, national and regional.s
Knowledge Unlatched
English
Keywords: Finance; Business & Economics; Finance